Author Correction: Synuclein and dopamine: the Bonnie and Clyde of Parkinson's disease. (July 2018) - Roy, Subhojit
In the version of this article initially published, the molecular mass of synuclein was given as 140 kDa instead of 14 kDa. The error has been corrected in the HTML and PDF versions of the article.